Adequacy and comprehensiveness of Zimbabwe’s Laws in combating child labour trafficking - Lasseko-Phooko, Matilda (University of Pretoria, 2024)
Mini Dissertaion (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2024.